2005
DOI: 10.1007/s00244-004-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pharmaceuticals on Aquatic Invertebrates. Part I. The Antiepileptic Drug Carbamazepine

Abstract: The effects of the antiepileptic drug carbamazepine (CBZ) were studied in three freshwater invertebrate species representing different taxonomic groups, life histories, and habitats in aquatic ecosystems. The oligochaete Lumbriculus variegatus was exposed by way of CBZ-spiked sediments at nominal concentrations between 0.625 and 10 mg/kg dry weight (dw) for 28 days. At the end of the test, reproduction and biomass were monitored as end points. The non-biting midge Chironomus riparius was exposed to CBZ in a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 40 publications
4
84
0
1
Order By: Relevance
“…These results are reported in Table 3. The results are in agreement with those obtained by other authors for this type of mussel samples (Oetken et al, 2005;Gagné et al, 2006).…”
Section: Analytical Performance Characteristicssupporting
confidence: 93%
“…These results are reported in Table 3. The results are in agreement with those obtained by other authors for this type of mussel samples (Oetken et al, 2005;Gagné et al, 2006).…”
Section: Analytical Performance Characteristicssupporting
confidence: 93%
“…Other authors found a similar pattern, where the chronic tests presented a higher toxicity than the acute tests (e.g. Oetken et al, 2005;Zhang et al, 2012). Moreover, chronic studies performed with environmental concentrations have shown that CBZ can affect multiple oxidative and biochemical pathways in bivalves, with significant deleterious effects (Martin-Diaz et al, 2009;Contardo-Jara et al, 2011;Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 63%
“…Another important issue concerning carbamazepine is that it can adsorb to sediments, in this way threat-ening aquatic organisms which feed on organic matter. Oetken et al [167] showed that exposure of the invertebrate Chironomus ripar-ius to this pharmaceutical through sediments caused a blockade of pupation and decreased emergence with EC50 values of 160 and 280 µg kg −1 of dry weight, respectively. Carbamazepine is ubiq-uitously present in the environment, having an extremely low removal rate in STPs (7%) [54] and consequently being detected in rivers [16,20,21,54,92] at concentrations up to 595 ng L −1 [92] (Table 5).…”
Section: Antiepilepticsmentioning
confidence: 99%